Teori dan Praktik Perdagangan Valuta Asing - Siti Zainap; Putri Aulia; Gita Dwi Lestari; Yuni Afira Lubis (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the theory and practice of foreign exchange trading from the perspective of international economics. The research employed a qualitative approach using a library research method by collecting data from books, scientific journals, and other relevant academic sources. Data were analyzed descriptively through the processes of data reduction, data presentation, and conclusion drawing. The findings indicate that the foreign exchange market plays a significant role as a medium for currency exchange, international trade, investment, and cross-border financial transactions. It also functions as an international payment mechanism, a means of transferring purchasing power between countries, a provider of international credit facilities, and a hedging instrument against exchange rate risks. Exchange rate determination is influenced by the interaction of supply and demand as well as various macroeconomic factors, including inflation, interest rates, trade balance, capital flows, and monetary policy. Therefore, a comprehensive understanding of the theory and practice of foreign exchange trading is essential for supporting economic decision-making in the era of globalization.